2015
DOI: 10.14689/ejer.2015.59.7
|View full text |Cite
|
Sign up to set email alerts
|

Contact Disturbances, Self-Esteem and Life Satisfaction of University Students: A Structural Equation Modelling Study

Abstract: Problem Statement: A literature analysis revealed that contact disturbances, self-esteem and life satisfaction have been examined in different studies separately. In particular, the researchers observed that the studies conducted on Gestalt contact disturbances are limited in number. In this study, the variables of contact disturbances, self-esteem and life satisfaction have been examined all together, and their correlations with one another will be examined though path analysis in the structural equality mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
5
0
3
Order By: Relevance
“…Taking into account the literature, in parellel with the relationship between I'm not OK-You're OK life position and life satisfaction it is seen that self-esteem contributes to life satisfaction among university students. The studies showed that the individuals with high self-esteem reported higher scores in life satisfaction than those with low self-esteem (Huo & Kong, 2014;Miller, Zivnuska, & Kacmar, 2019;Tagay, 2016).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Taking into account the literature, in parellel with the relationship between I'm not OK-You're OK life position and life satisfaction it is seen that self-esteem contributes to life satisfaction among university students. The studies showed that the individuals with high self-esteem reported higher scores in life satisfaction than those with low self-esteem (Huo & Kong, 2014;Miller, Zivnuska, & Kacmar, 2019;Tagay, 2016).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Neto ve Mullet (2004) tarafından lisans öğrencileri ile yürütülen bir araştırmaya göre başkalarını affetme ile başkalarına bağımlı benlik kurgusuna sahip olmanın affetmeyi kolaylaştırdığı sonucuna ulaşılmıştır. Tagay (2015) tarafından lisans öğrencileri üzerinde yapılan bir araştırmada gestalt temas engellerinin benlik saygısını; benlik saygısının da yaşam doyumunu etkilediği görülmüştür. Ayrıca araştırmanın sonuçları incelediğinde bağımlı temas aşamasında engel yaşayanların benlik saygısının yüksek olduğu görülmektedir.…”
Section: Başkalarını Affetmeye İlişkin Sonuçlarunclassified
“…Individuals with high self-esteem respect themselves, have close relationships and have strong coping skills (Baumeister et al, 2003;Rosenberg, 1965;Sam et al, 2010). When the literature focusing on issue of self-esteem is examined, it is seen that there are studies investigating the relationships between self-esteem and contact obstacles and life satisfaction (Tagay, 2015); loneliness and psychological well-being (Güloğlu and Karaırmak, 2010); and communication skills and psychological well-being (Tagay and Karakelle, 2014).…”
Section: Authors Agree That This Article Remain Permanently Open Accementioning
confidence: 99%